Technology Acceptance Model for Business Intelligence System - Saud, Subin (Nepalese Journal of Economics, 2025)
This study examines technology acceptance model for business intelligence system. Business intelligence system is selected as the dependent variable. Similarly, customer’s attitude, perceived usefulness, subjective norms, perceived ease of use and social values are selected as the independent variables. This study is based on primary data with 111 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing the technology acceptance for business intelligence system. The study showed that customer attitude is positively correlated to the business intelligence system. It indicates that increase in consumer attitude leads to the increase in technology acceptance for business intelligence system. Similarly, perceived usefulness is positively correlated to the business intelligence system indicating that perceived usefulness increases technology acceptance for business intelligence system. Moreover, subjective norms are also positively related to the business intelligence system. It means that better the subjective norms better will be the technology acceptance model for business intelligence system. Likewise, perceived ease of use is positively correlated to the business intelligence system. It shows that increase in perceived ease of use leads to the increase in technology acceptance for business intelligence system. Further, social value has a positive impact on the business intelligence system. It shows that better the social value better will be the business intelligence system.